The changing international linkages of Switzerland: An overview - Cédric Tille (Kiel Institute for the World Economy (IfW), 2017)
Over the last decade, the economic linkages between Switzerland and the rest of the world have been transformed. First, merchanting and the chemical industry account for an increasing share of international trade, with chemicals exports expanding robustly in recent years despite the European crisis and the strong Swiss franc. Second, the nature of international financial integration has changed. While private investors drove Switzerland's financial flows and net foreign assets before the financial crisis, the foreign reserves accumulation by the Swiss National Bank has been playing a major role since. Third, asset prices and foreign exchange movements led to substantial capital losses in foreign assets which fully absorbed the surplus on the current account. Finally, the crisis has weakened the role of foreign trade as an engine of growth and narrowed it across sectors.
Keywords: F1; F4; 330; Switzerland; current account; globalization; external investment position